POLA PENYELENGGARAAN KEAKSARAAN DASAR SEBAGAI PROGRAM PENDIDIKAN NON FORMAL (Studi Kasus di SKB Bulukumba): (Studi Kasus di SKB Bulukumba) - Ilmar Andi Achmad; Muhammad Athar Asmas (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2019)
A number of people in big cities today have tended to have different educational institutions were seen as more feasible and more appropriate for their children to attend school, educational institutions are called LCS. Bulukumba as one tourist city in Indonesia already has a community organizer for such an educational institution. Studio Learning Activities (SKB) which is located in Bulukumba shaft is one of the organizing institutions Basic Literacy (KD), which is well known and is a best practice to the institutions. Therefore these institutions should be reviewed and problems that need to be raised is how the home school operations carried out in the institution. This study aims to gain an overview of (1) the pattern of implementation SKB, especially with respect to curriculum, workforce, students, infrastructure, financing, institutional, and partnerships, and (2) the pattern of Education held in